The Impact of Migration Processes on Economic Security and Space Development of Russia - L. S. Arkhipova; I. V. Gorokhova (Вестник Российского экономического университета имени Г. В. Плеханова)
The topicality of researching specific features of migration processes on the territory of the Russian Federation deals with the rising role of economic security in providing strategic priorities of states in the period of growing tension in the world. Apart from that, such factors as unfavorable demographic situation, changes in the age structure of the population, adverse trends on labour market of many regions, shortage of labour, etc. become more and more important. It increases academic and practical interest in researching migration processes on different territorial levels, including the sphere of national and economic security. The Decree of the President of the Russian Federation N 208 dated May 13, 2017 ‘Concerning Strategy of Economic Security in the Russian Federation for the Period up to 2030’ defined optimization of labour migration flows based on needs of national economy as one of key objectives of realizing the trend dealing with the development of state governance system, forecasting and strategic planning in economy.  This document among indicators characterizing economic security focuses on the tension factor on labour market, the share of employable people in the total population and distribution of those employed by the level of education. The Degree of the President of the Russian Federation N 400 dated July 2, 2021 ‘Concerning Strategy of National Security of the Russian Federation’ points out that attaining goals of economic security of the Russian Federation is realized by solution of such important problems as cutting differentiation of entities of the Russian Federation by the level and rate of social and economic development, standard of living, motivating the development of economic potential in regions, strengthening of their budget support. Migration processes are included in the zone of such problem solution. They can cause even higher territorial differentiation in regions, a drop in the standard of life or, on the contrary, reduce territorial inequality and improve space development of the country. In view of national and economic security external migration is more important, as it influences many social and economic aspects taking place in the country. But whether migration processes inside the country can affect economic security of Russia is still a debatable issue.